Pengaruh akuntabilitas pengelolaan dan optimalisasi penggunaan dana desa terhadap pengembangan badan usaha milik gampong (BUMG) - Zamzami Zamzami; Rina Maulina (Akuntansi dan Teknologi Informasi, 2023)
Village funds are essential for development; therefore, it is crucial to look into their management and use. This study aims to examine the impact of accountability in managing village funds and optimizing the use of village funds on the growth of village-owned enterprises (a case study in Padang Rubek Village, Kuala Pesisir District, Nagan Raya District). Methods for collecting data include conducting surveys and obtaining as many as 25 respondents. Using a questionnaire, survey data were collected, processed, and analyzed using multiple linear regression tests. The Pearson Correlation Validity Test and the Cronbach Alpha Reliability Test are used to assess the quality of the data for this study. Applying multiple linear regression to data. The findings of this study indicate that the accountability of village fund management has a positive and significant impact on the development of gampong-owned businesses. Moreover, optimizing the use of village funds has a substantial positive impact on the growth of gampong businesses. This result suggests that village-owned enterprises can develop further if village funds are managed appropriately.